(untitled) - Duell, Ryan (New Jerey, 2015)
This new edition includes expanded information on rendering and visualization, and a new discussion surrounding effective work sharing, details and annotations, drawing sets, and professional workflows. The companion website features additional tutorials, plus downloadable data sets that allow you to jump in at any point and compare your work to the pros.
Keywords: Thiết kế kiến trúc,Autodesk Revit.,Architectural drawing,Architectural design,Bản vẽ kiến trúc; Xử lý dữ liệu,Computer-aided design.,Data processing,Máy tính hỗ trợ thiết kế.